Design, fabrication, optimization and characterization of memantine-loaded biodegradable PLGA nanoscaffolds for treatment of Alzheimer’s disease - Rani V.; Chawla R. (My University, 2025)
This study aimed to design and develop nanoscaffolds for the controlled release of memantine by non-solvent-induced phase separation (N-TIPS) method. The development and optimization of nanoscaffolds was performed by Box-Behnken Design in which two independent formulation variables and one independent process variable: poly(lactic-co-glycolic acid) (PLGA) (X 1), Pluronics F-127 (X 2), and rotation speed (X 3) were used. The design provided 15 formulation designs which were prepared to determine the response: percentage porosity (Y 1) and drug loading (Y 2). Polynomial equations were generated and analyzed statistically to establish a relationship between independent and dependent variables and develop an optimal formulation with maximized porosity (%) and drug loading (%). The optimized formulation batch was prepared using 19.18% w/v PLGA, 4.98% w/v Pluronics at 500 rpm rotation speed and exhibited drug loading of 11.66% and porosity of 82.62%. Further, correlation between the independent and dependent variables were established and statistically analyzed by using model generated mathematical regression equations, ANOVA, residual plots, interaction plot, main effect plot, contour plot and response surface designs. The analysis of model showed the significant individual effect of PLGA and significant interactive effect of Pluronics F-127 and rotation speed on drug loading and porosity. Further, its physicochemical characterization, and in-vitro (drug release kinetics, and PAMPA study), ex-vivo (enzyme inhibition assay and pro-inflammatory cytokines study) and in-vivo (neurobehavioral and histological study) studies were performed to evaluate the potential of memantine-loaded nanoscaffolds in the treatment of Alzheimer’s disease (AD). © 2022 IOP Publishing Ltd.